2017
DOI: 10.1089/jayao.2017.0037
|View full text |Cite
|
Sign up to set email alerts
|

Cancer-Related Fatigue in Adolescents and Young Adults After Cancer Treatment: Persistent and Poorly Managed

Abstract: Cancer-related fatigue is the most prevalent and distressing symptom experienced by adolescents and young adults (AYAs). An electronic survey was undertaken to ascertain current fatigue management and perceptions of its effectiveness. Eighty-five percent of responders (68/80) experienced fatigue, and it was worse more than 1 year after cancer treatment ended, compared to <1 year (p = 0.007). Forty-one percent received no fatigue management. Although advice to exercise was the most frequent intervention, the gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
43
1
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 44 publications
(47 citation statements)
references
References 21 publications
1
43
1
2
Order By: Relevance
“…However, our results revealed that cALL survivors commonly reported vitality/fatigue, sleeping, and discomfort/symptoms issues while several other health domain issues were specific to either age subgroups (e.g., appearance in adolescents and mental function in adults). Cancer‐related fatigue and sleep problems (sleep disturbance, sleep quality, and daytime sleepiness) are among the most common late effects following cancer . If left unmanaged, they can yield important work or school performance difficulties, which may lead to significant distress, anxiety, depression, and impaired quality of life .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, our results revealed that cALL survivors commonly reported vitality/fatigue, sleeping, and discomfort/symptoms issues while several other health domain issues were specific to either age subgroups (e.g., appearance in adolescents and mental function in adults). Cancer‐related fatigue and sleep problems (sleep disturbance, sleep quality, and daytime sleepiness) are among the most common late effects following cancer . If left unmanaged, they can yield important work or school performance difficulties, which may lead to significant distress, anxiety, depression, and impaired quality of life .…”
Section: Discussionmentioning
confidence: 99%
“…Cancerrelated fatigue and sleep problems (sleep disturbance, sleep quality, and daytime sleepiness) are among the most common late effects following cancer. [63][64][65][67][68][69][70][71] If left unmanaged, they can yield important work or school performance difficulties, which may lead to significant distress, anxiety, depression, and impaired quality of life. [72][73][74][75][76] In fact, sleeping issues seemed to be key contributors to psychological health: both adolescents and adults in the present study were 2 to 10 times more likely to report anxiety, depression or distress if they had sleeping difficulty.…”
Section: Discussionmentioning
confidence: 99%
“…Fatigue was reported to be a common problem for AYA when they finished their cancer treatment (Hauken et al, 2013;Moody et al, 2015;Ruccione et al, 2013;Spathis et al, 2017;Thompson et al, 2009). Hauken et al (2013) highlighted fatigue as one of the biggest physical issues, with consequences on other aspects of life, such as an AYA's ability to build and sustain relationships (Thompson et al, 2009) and to concentrate at school (Choquette, Rennick, & Lee, 2016).…”
Section: Physical/medical Issues At the End Of Treatmentmentioning
confidence: 99%
“…Cancer in adolescent and young adults (AYA), generally accepted internationally as those aged 15–39 years at diagnosis (Bleyer, Barr, Reis, Whelan, & Ferrari, ), presents unique challenges. For some time, the ongoing physical and psychosocial needs of AYA living with and beyond cancer have been studied (Galan et al, ; Spathis et al, ; Zebrack, Chesler, & Penn, ), and while there has been much written about the provision of long‐term follow‐up care, and models proposed to address these needs (Docherty, Kayle, Maslow, & Santacroche, ; Hiers et al, ; Shay, Parsons, & Vernon, ), there has been less focus on the point where active, curative treatment ends.…”
Section: Introductionmentioning
confidence: 99%
“…Although the overall outlook for adolescents and young adults diagnosed with cancer (AYAs) is improving, AYAs face several challenges. Receiving a potentially life‐threatening diagnosis during a time when chronic diseases such as cancer are atypical (ie, during adolescence and young adulthood) and having to endure a myriad of negative physical, biological, psychological, and social effects caused by treatments responsible for survival can greatly impair their health, functioning, and quality of life . Indeed, many AYAs experience problems as they progress through the cancer continuum (ie, diagnosis, treatment, and survival).…”
Section: Introductionmentioning
confidence: 99%